Defining a population:|women and children in early republican Turkey, 1923-1950 - Öztamur, Pınar. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This thesis looks at the construction of welfare, and women and children as objects of welfare practices, new sciences, technologies and arts of government in early Republican Turkey and covers a period between the late 1920s and the 1940s. Following World War I and the Independence War and in the climate of the nation-state building, several actors in Republican Turkey, including state authorities, intellectuals, physicians and others, were concerned with the size, rate of growth and "quality" of the population as an object of government and management. These new forms of government, which primarily intended to confront the problem of population decline, targeted several objects which included the regulation of the social and employed techniques such as censuses, social insurance, urban planning and housing projects and problematized the city, the home, the family as well as the individual body as objects of their projects. Among these objects, this thesis is primarily concerned with women and children, and the policies and practices targeting them. Through the lens of womanhood, motherhood and childhood, this thesis presents discussions, on a broad scale, of Turkish state and society in a period of the nation-state building and the ongoing efforts to transform society by the Republican elites. The Republican elite's obsession with the concepts of childhood and proper womanhood and motherhood went hand in hand with their obsession with nationhood and modernity. Like woman's bodies, children's bodies promised a field which bore possibilities for the Republican elite to chart their aspirations in the path of nation-state building and symbolized the severed ties with a distant imperial past, which they strove to forget.